ANALYZING THE FACTORS THAT TRIGGER CONSUMERS HEDONIC MOTIVATION IN CHOOSING LOCAL COFFEE SHOPS AND FRANCHISED COFFEE SHOPS IN MANADO - Sangian, Yosua G.; Pangemanan, Sifrid S.; Pandowo, Merinda H. C. (Universitas Sam Ratulangi, 2020)
The number of coffee shops in the city of Manado, which grows mainly in 2005, provides an opportunity for marketers competing for consumers. Many companies start doing cafÃ© business in 2011, but the every business have competitor as always such as the franchise coffee shops, Starbucks, Dunkin Donuts and the local coffee.This research aims to analyzing the factor that trigger consumers hedonic motivation in choosing local coffee shops and franchised coffee shops in manado, With 100 Respondent. And the Factor Analysis method is used in this research. There are three most dominant factors out of twenty factors (Cleanless Appealing Aroma Adequate Lighting Comfortable Furniture View to Outside Brand and Product of Origin Service Staff Behavior Wi-fi Connection Promotion Trust And Respect Lifestyle Opportunity to Linger Menu Variety Taste and Ingredients Appealing Music) and three highest factors that have big impact on consumers hedonic motivation in choosing local coffee shops and franchised coffee shops in Manado, which are Price, Appealing Decor, and Appearence and Presentation, Based on communality test, the highest value is Price, followed by Appealing decor, and Appearence and Presentation.Keywords: Marketing, Consumers Behavior, Consumer Hedonic Motivation, Consumer Purchase Decisions, Coffee Shops